9 CASES OF AMYAND'S HERNIA IN CHILDREN - M.KH. MALIKOV; F.SH. RASHIDOV; F.B. BOKIEV; F.M. KHAMIDOV (Avicenna Tajik State Medical University, 2021)
9 children aged 4 to 14 years underwent a right-sided inguinal hernia repair, at the same time, a vermiform appendix was found in the hernial sac. All patients were hospitalized with a diagnosis of «Congenital right-sided inguinoscrotal hernia», bilateral hernias were not observed. Objectively, there were all signs of the disease, all hernias were reducible. The presence of the appendix in the hernial sac before the operation was not diagnosed either clinically or by ultrasound. The contents of the hernial sac had a thickened and long vermiform appendix, a greater omentum, and in two cases - a cecum of the type of sliding hernia. The children were operated on under general anesthesia: appendectomy and plastic surgery of posterior wall of inguinal canal were performed. No complications were observed in the postoperative period.